Hubungan Pengetahuan dan Lama Pengobatan TB Paru dengan Kepatuhan Minum Obat pada Pasien TB Paru Di Klinik Harum Melati - Dwiningrum, Riza; Wulandari, Rizki Yeni; Yunitasari, Eva (Universitas Aisyah Pringsewu, 2021)
Pulmonary TB disease in Indonesia is a serious problem, the number of confirmed pulmonary TB patients in Indonesia has increased significantly. In 2018, there were 511.873 cases of pulmonary TB in Indonesia, 294.757 cases for men and 217.116 cases for women. The success rate of treatment in Indonesia in 2018 was only 87.12% of the national target of 90%. Preliminary study at the Harum Melati Clinic, of 60 patients 35 were old patients who were undergoing treatment in the advanced phase and 25 were new patients undergoing intensive phase of treatment. From 25 people out of 60 patients undergo the lack of knowledge about TB. The research objective was to determine the correlation between knowledge and duration of treatment with medication adherence in pulmonary TB sufferers at the Harum Melati Clinic 2021. This type of research was quantitative research with descriptive correlation design using a cross sectional approach. The population of this research was pulmonary TB patients at the HarumMelati Clinic, Gadingrejo as many as 60 people, all of which were used as samples. This research used the Chi Square hypothesis test. The results showed that there was correlation between knowledge and medication adherence on TB patients at the HarumMelati Clinic in 2021, as evidenced by p-value = 0.001 less than 0.05 with an OR value of 6.000. There was correlation between knowledge and medication adherence on TB patients at the HarumMelati Clinic in 2021, as evidenced by p-value = 0.001 less than 0.05 with an OR value of 2.667. It is recommended for health workers to provide information to pulmonary TB sufferers and their families about the importance of routinely taking medication in an effort to accelerate the healing process.Penyakit TB paru di Indonesia merupakan masalah yang serius, jumlah pasien TB paru di Indonesia terkonfirmasi mengalami peningkatan signifikan. Pada tahun 2018 tercatat kejadian TB paru di Indonesia sebanyak 511.873 kasus, laki-laki sebanyak 294.757 kasus dan perempuan sebanyak 217.116 kasus. Angka keberhasilan pengobatan di Indonesia pada tahun 2018 hanya sebesar 87,12% dari target nasional sebesar 90%. Studi pendahuluan di Klinik Harum Melati, dari 60 pasien 35 orang adalah pasien lama yang sedang menjalani pengobatan pada fase lanjut dan 25 orang lainnya adalah pasien baru yang menjalani pengobatan fase intensif. 25 orang dari 60 pasien mengalami kurang pengetahuan tentang TB. Tujuan penelitian ini adalah diketahui hubungan pengetahuan dan lama pengobatan dengan kepatuhan minum obat pada pasien TB Paru di Klinik Harum Melati Tahun 2021. Jenis penelitian ini merupakan penelitian kuantitatif dengan desain deskriptif korelasi menggunakan pendekatan cross sectional. Populasi penelitian ini adalah pasien TB paru di Klinik Harum Melati Gadingrejo sebanyak 60 orang yang seluruhnya dijadikan sampel. Penelitian ini menggunakan uji hipotesis Chi Square. Hasil penelitian menunjukkan bahwa ada hubungan pengetahuan dengan kepatuhan minum obat pada pasien TBC di Klinik Harum Melati Tahun 2021 dibuktikan p-value = 0,001 kurang dari 0,05 dengan OR didapatkan nilai 6.000. Ada hubungan pengetahuan dengan kepatuhan minum obat pada pasien TBC di Klinik Harum Melati Tahun 2021 dibuktikan p-value = 0,001 kurang dari 0,05 dengan OR didapatkan nilai 2.667. Disarankan kepada petugas kesehatan untuk memberikan informasi kepada penderita TB paru dan keluarga tentang pentingnya rutin meminum obat sebayai upaya mempercepat proses kesembuhan.